2000
DOI: 10.1161/01.cir.101.14.1686
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Right Ventricular Volume Overload Increases Myocardial Fluorodeoxyglucose Uptake in the Interventricular Septum in Patients With Atrial Septal Defect

Abstract: Background-Several-(p-iodophenyl)-3-R,S-methylpentadecanoic acid (BMIPP) in 11 patients with atrial septal defect (ASD) and 11 control subjects. In the FDG study, we calculated myocardial metabolic rate of glucose (MMR) in interventricular septum (IVS) and left ventricular (LV) free wall. MMR was significantly increased in IVS compared with LV free wall in the ASD patients (420Ϯ35 versus 333Ϯ32 mol ⅐ kg Ϫ1 ⅐ min Ϫ1 ; PϽ0.05) but not in the control group (347Ϯ27 versus 357Ϯ25 mol ⅐ kg Ϫ1 ⅐ min Ϫ1 ). In both ASD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In right ventricular (RV) pressure overload due to pulmonary artery constriction in rats, we demonstrated not only that myocardial glucose utilization in the RV free wall increased, but the regional profiles of substrate utilization in the interventricular septum and the LV free wall were also altered (5). Our previous clinical study with positron emission tomography (PET) demonstrated that myocardial [ 18 F]fluorodeoxyglucose (FDG) accumulation was increased in the interventricular septum compared with the LV free wall in patients with chronic RV volume overload due to atrial septal defect, and that the FDG accumulation in the RV free wall was also increased in those patients compared with the control subjects, although we did not correct the radioactivity for the RV free wall thickness (7). However, it is unclear whether FDG accumulation in the RV free wall, corrected for the partial volume effect, which is derived from the relatively thin RV free wall thickness, increases in patients with chronic RV pressure overload.…”
mentioning
confidence: 94%
“…In right ventricular (RV) pressure overload due to pulmonary artery constriction in rats, we demonstrated not only that myocardial glucose utilization in the RV free wall increased, but the regional profiles of substrate utilization in the interventricular septum and the LV free wall were also altered (5). Our previous clinical study with positron emission tomography (PET) demonstrated that myocardial [ 18 F]fluorodeoxyglucose (FDG) accumulation was increased in the interventricular septum compared with the LV free wall in patients with chronic RV volume overload due to atrial septal defect, and that the FDG accumulation in the RV free wall was also increased in those patients compared with the control subjects, although we did not correct the radioactivity for the RV free wall thickness (7). However, it is unclear whether FDG accumulation in the RV free wall, corrected for the partial volume effect, which is derived from the relatively thin RV free wall thickness, increases in patients with chronic RV pressure overload.…”
mentioning
confidence: 94%
“…The increase 7 in metabolic uptake in the interventricular septum in FDG-PET scans has been observed in patients with atrial septal defect but again there is no report about occurrence of septal flattening. 18 We present the first observational study of eight patients who showed flattening of the interventricular septum during gated SPECT imaging with echocardiographic confirmation of pulmonary hypertension or right ventricular overload. Interestingly, despite significant pulmonary hypertension in the majority of the patients with flattening of the septum seen on gated SPECT imaging, only 50% had septal flattening documented by echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been similarly recapitulated in humans as well. In a small study, an increase in glucose uptake in the interventricular septum relative to the LV free wall of atrial septal defect patients was seen compared with controls as assessed by FDG-PET, which correlated with indices of RV overload [47]. Oikawa et al hypertension and the response to treatment.…”
Section: Imaging Right-ventricular Metabolismmentioning
confidence: 92%